On John Stuart Mill - Kitcher, Philip, 1947- (Columbia University Press, 2023)
"When reading John Stuart Mill, it's easy to have a sense of "déja vu all over again." At first sight, his ideas seem completely familiar, well understood, and thoroughly absorbed in the way we live now. Do we need him to explain the advantages of free speech and open debate? Or to emphasize attending to the consequences of actions? To protect differences that don't harm others, and to plead for equality of opportunity? Even if he once counted as "dangerous" or "subversive", he can appear all too tame today. On John Stuart Mill aims to approach him differently - not by rehearsing his (considerable) contributions to contemporary attitudes, but by starting just where the ideas he has bequeathed to us seem most problematic. Our own political debates hardly approximate the conditions envisaged in the famous defense of free speech. If we read more closely - and more widely - it becomes evident that he was already aware of the problem, and that he struggled to reconcile the claims of democracy with the importance of expertise. Those struggles can help us as we wrestle with kindred difficulties. In this extended, and beautifully written, essay, Kitcher develops some of Mill's ideas in the context of contemporary ethical, social, and political issues and debates, and what he would have made of them. These debates--such as those around government mandated Covid-19 masks and vaccines, Second Amendment worship, income inequality, gay marriage, and climate change--involve questions of individual freedom, free speech, equality, and utilitarianism, all of which are central to Mill's project. In doing so, Kitcher draws primarily, though not exclusively, on the three works by Mill (sometimes in close collaboration with Harriet Taylor) that typically feature on the Contemporary Civilization syllabus: On Liberty, Utilitarianism, and The Subjection of Women. He also discusses Mill's Principles of Political Economy. By focusing on questions that are salient today, he hopes to capture the tone of exploratory conversations at which Contemporary Civilization aims"-- Provided by publisher.
Keywords: Mill, John Stuart, -- 1806-1873.; Mill, John Stuart, -- 1806-1873; PHILOSOPHY / Movements / Utilitarianism; Electronic books.